Characterizing Radon Among Public Buildings and Small/Medium-Sized Businesses in a Canadian Province - Lily X. Yang; Tracy L. Kirkham; Laura Boksman; Anne-Marie Nicol; Paul A. Demers (Atmosphere)
Radon is a naturally occurring radioactive gas that causes lung cancer. It has been measured extensively in homes and mines but research in other workplaces has been limited. The present study examined 453 workplaces in Ontario, Canada, to characterize radon levels. Radon monitors (n = 687) were placed in occupied ground floor and basement workplace locations for a minimum of three months. The radon measurements ranged from <4 to 566 Bq/m3, with a median of 26 Bq/m3, arithmetic mean of 40.2 Bq/m3, and geometric mean of 26.9 Bq/m3. Using the Health Canada and Ontario labor guideline of 200 Bq/m3, 2.5% of participating workplaces had at least one measurement above this level; 7.2% were above the World Health Organization guideline. Workplaces were also asked to fill out questionnaires to identify possible determinants of exposure. Radon levels varied significantly based on municipality and background radon zone, highlighting the importance of geography in influencing radon levels. Radon levels also varied significantly based on window-opening behavior, business access type, the presence of an elevator, air conditioning, additions to the building, and cracks and/or gaps in the foundation/wall and around drains, indicating building characteristics with some influence on air circulation may impact overall radon levels.